Pajak Hotel dan Pajak Hiburan Terhadap Pendapatan Asli Daerah Pada Badan Pendapatan Daerah Kota Makassar - Syamsuriana, Nur; Ismawan, Ismawan (Jurnal Ilmiah Manajemen & Kewirausahaan, 2024)
This research is important because it can provide an in-depth understanding of the effect of hotel tax and entertainment tax on local original income. It can also be the basis of policies for local governments to increase revenues and local development. This type of research is a quantitative type, because the data is realized in the form of numbers and analyzed through statistical analysis, with the aim of determining the influence of independent variables, namely Hotel Tax, and Entertainment Tax on the dependent variable, namely Regional Original Income (PAD) of Makassar City in 2019-2023. The test results that have been carried out using multiple linear regression analysis tests with data processing using SPSS 25 show that these results state that hotel tax and entertainment tax have a significant influence on local original income, but on the entertainment tax variable the effect is not positive but negative because the realization of revenue in entertainment tax is very low.